PENGGUNAAN LAYANAN KONSELING KELOMPOK UNTUK MENGURANGI KENAKALAN REMAJA PADA SISWA KELAS VIII - Noviya Sari; Giyono Giyono; Ari Sofia (ALIBKIN (Jurnal Bimbingan Konseling), 2015)
The purpose of this study was to determine whether the group counseling services with client-centered approach can reduce students' juvenile delinquency. Problems in this study was the juvenile delinquency. And the issue was